Predicting the Characteristics of a Human from Facial Features by Using SURF - Nagaral, Mahesh U; Reddy, T. Hanumantha (International Journal of Computer Sciences and Engineering, 2018)
In the modern society everybody wants to be familiar with people’s characteristics to predict and be aware of their reaction to diverse situation, though it’s hard to understand psychological nature and characteristics of a person. For this reason, researches have been carried out in this direction to predict the characteristics of a person such as maturity, warmth, intelligence, sociality, dominance, as well as the trustworthiness. Here aim is to identify person’s characteristics based on the facial features by using techniques such as SURF, which is going to be used for the extraction of the facial features and Knearest neighbor classifier for identification of the characteristics of the human being. With the various features mentioned and by using the appropriate techniques, the characteristics of a person can be predicted. The overall performance of the proposed work has been estimated by well established dataset and results show that the proposed work has performed well.